2017
DOI: 10.1007/s00259-017-3659-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk-stratifying capacity of PET/CT metabolic tumor volume in stage IIIA non-small cell lung cancer

Abstract: Objectives Stage IIIA non-small cell lung cancer (NSCLC) is heterogeneous in tumor burden, and its treatment is variable. Whole-body metabolic tumor volume (MTVWB) has been shown to be an independent prognostic index for overall survival (OS). However, the potential of MTVWB to risk-stratify stage IIIA NSCLC has previously been unknown. If we can identify subgroups within the stage exhibiting significant OS differences using MTVWB, MTVWB may lead to adjustments in patients’ risk profile evaluations and may, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Studies on the survival effect of baseline MTV are relatively limited. Investigators from the University of Chicago concluded that PET-MTV was more important than AJCC staging, and PET-MTV can further predict survival for each stage group such as IIIA [20,21]. Another study reported that a smaller MTV on FDG-PET was associated with epidermal growth factor receptor (EGFR) mutations and better survival [22].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the survival effect of baseline MTV are relatively limited. Investigators from the University of Chicago concluded that PET-MTV was more important than AJCC staging, and PET-MTV can further predict survival for each stage group such as IIIA [20,21]. Another study reported that a smaller MTV on FDG-PET was associated with epidermal growth factor receptor (EGFR) mutations and better survival [22].…”
Section: Discussionmentioning
confidence: 99%
“…From the database of our institutional Cancer Center Cancer Registry, we found 2,510 patients with NSCLC who were diagnosed with pathological confirmation and treated at our institution from January 2004 to December 2014. Part of this patient population was previously analyzed for different purposes and reported [25, 15, 16]. The patients were enrolled based on the following inclusion criteria: 1) had undergone a baseline FDG PET/CT with PET positive tumor, 2) had no evidence of brain metastasis, and 3) did not have concurrent diagnosis or a history of other primary cancer[17].…”
Section: Methodsmentioning
confidence: 99%
“…However, it cannot be easily used clinically as an interval measurement. Although MTV wb has been used for risk stratification within TNM stages[3, 6, 7, 1316], the MTV wb cutoff points in various studies were different for the same TNM stages due to heterogeneity of the tumor burden[6, 7, 16]. Based on the independent prognostic value of the MTVwb and the variation of the patient survival within the same TNM stage, we hypothesized that the MTVwb could be used clinically to supplement NSCLC staging through risk stratification, and so developed and validated a novel MTVwb risk stratification system for use in conjunction with the TNM staging system and other prognostic variables.…”
Section: Introductionmentioning
confidence: 99%
“…Another study including only NSCLC patients in stage III reported the use of whole-body MTV to stratify patients for the adoption of the most appropriate therapeutic strategy [ 58 ]. The authors found that volume-based PET parameters may help to choose whether a patient in stage IIIA should receive a more aggressive treatment than that for stage IIIB or a less intensive regimen than that for stage IIB.…”
Section: The Prognostic Role Of Volume-based Pet Parameters In Allmentioning
confidence: 99%